Suppression of methane uptake by precipitation pulses and long-term nitrogen addition in a semi-arid meadow steppe in northeast China - Gao, Weifeng; Yang, Xu; Zhang, Yicong; Zhao, Tianhang; Shi, Baoku; Yang, Tianxue; Ma, Jianying; Xu, Wanling; Wu, Yining; Sun, Wei (Frontiers in Plant Science, 2023)
In the context of global change, the frequency of precipitation pulses is expected to decrease while nitrogen (N) addition is expected to increase, which will have a crucial effect on soil C cycling processes as well as methane (CH4) fluxes. The interactive effects of precipitation pulses and N addition on ecosystem CH4 fluxes, however, remain largely unknown in grassland. In this study, a series of precipitation pulses (0, 5, 10, 20, and 50 mm) and long-term N addition (0 and 10 g N m-2 yr-1, 10 years) was simulated to investigate their effects on CH4 fluxes in a semi-arid grassland. The results showed that large precipitation pulses (10 mm, 20 mm, and 50 mm) had a negative pulsing effect on CH4 fluxes and relatively decreased the peak CH4 fluxes by 203-362% compared with 0 mm precipitation pulse. The large precipitation pulses significantly inhibited CH4 absorption and decreased the cumulative CH4 fluxes by 68-88%, but small precipitation pulses (5 mm) did not significantly alter it. For the first time, we found that precipitation pulse size increased cumulative CH4 fluxes quadratically in both control and N addition treatments. The increased soil moisture caused by precipitation pulses inhibited CH4 absorption by suppressing CH4 uptake and promoting CH4 release. Nitrogen addition significantly decreased the absorption of CH4 by increasing NH4+-N content and NO3–N content and increased the production of CH4 by increasing aboveground biomass, ultimately suppressing CH4 uptake. Surprisingly, precipitation pulses and N addition did not interact to affect CH4 uptake because precipitation pulses and N addition had an offset effect on pH and affected CH4 fluxes through different pathways. In summary, precipitation pulses and N addition were able to suppress the absorption of CH4 from the atmosphere by soil, reducing the CH4 sink capacity of grassland ecosystems.